Rating indicators as criteria for academic excellence in higher education: Kazakhstani context (Journal of Educational Sciences, 2024)
The article is devoted to the assessment of criteria and indicators for measuring academic excellence within the framework of the international system of assessment of university education. The article examines existing evaluation criteria, including the role of rating systems, and presents examples of foreign initiatives that analyze their interaction with rating assessments. The authors also discuss the idea of creating a Center of Academic Excellence (CAE) in Kazakhstan, based on global experience in implementing academic excellence initiatives. Particular attention is paid to the analysis of the starting positions of Kazakhstani universities according to rating indicators, which allows us to draw conclusions about the current state of the academic sector in the country and its place in the global context. Based on expert interviews with top management and teaching staff of leading Kazakhstani universities, the main criteria of academic excellence and their correlation with rating indicators are identified. The article also carried out a SWOT analysis of the position of Kazakhstani universities in the QS World University Rankings 2024 according to key indicators. The research methodology is based on grounded theory applied in qualitative methods. The practical significance of the results of the work lies in the formation of recommendations for improving the positions of Kazakhstani universities in international rankings and strengthening their competitiveness at the global level.Key words: rating criteria, indicators, academic excellence, center of academic excellence.